The history of the Catholic Church in Latin America: from conquest to revolution and beyond - Schwaller, John Frederick (New York Univ. Press, 2011)
Religious origins of Catholicism in Latin America -- Spain and Portugal in the the New World -- Conquest, spiritual and otherwise -- The colonial church -- Reform and enlightenment -- The church and clergy at independence -- Working out the differences -- The established order and the threat of popular religion -- Revolution and reform -- The mid-twentieth-century church -- The decline of liberation theology